FORECASTING MODEL OF ONIONS IN SUMBAWA DISTRICT - Susilawati, Tri; Darmawan, Indra; Ardiansyah, Eka; Adlimi, Arsil (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2023)
Sumbawa Regency as the second largest shallot producing area in NTB certainly contributes to food security in Sumbawa Regency in particular and in Indonesia in general. This condition certainly needs to make policy makers predict crop yield growth for the following years. This study aims to predict shallot yields for the next 9 years. The data used is secondary data sourced from the Sumbawa District Agriculture Office. There are three trend forecasting methods used, namely least square method, quadratic and exponential trend models. Based on the calculation results, the best forecasting trend model is obtained, namely the exponential trend model with MAPE and MAD values ​​and the largest coefficient of determination (R2). The exponential trend obtained shows a positive trend, namely positive exponential values ​​and positive principal numbers